2006
DOI: 10.1271/bbb.60036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of DietaryD-Psicose on Diurnal Variation in Plasma Glucose and Insulin Concentrations of Rats

Abstract: The effects of supplemental D-psicose in the diet on diurnal variation in plasma glucose and insulin concentrations were investigated in rats. Forty-eight male Wistar rats were divided into four groups. Each group except for the control group was fed a diet of 5% Dfructose, D-psicose, or psico-rare sugar (3:1 mixture of D-fructose and D-psicose) for 8 weeks. Plasma glucose levels were lower and plasma insulin levels were higher at all times of day in the psicose and psico-rare sugar groups than in the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 22 publications
4
64
0
2
Order By: Relevance
“…8) Recent reports also confirm that D-psicose can prevent post-prandial hyperglycemia in diabetic rats by lowering plasma glucose levels and reducing body fat accumulation. 9) These physiological properties make D-psicose a potential alternative sweetener, but more intensive studies of it have been impeded by its unavailability. There have been few reports on the chemical synthesis of D-psicose.…”
mentioning
confidence: 99%
“…8) Recent reports also confirm that D-psicose can prevent post-prandial hyperglycemia in diabetic rats by lowering plasma glucose levels and reducing body fat accumulation. 9) These physiological properties make D-psicose a potential alternative sweetener, but more intensive studies of it have been impeded by its unavailability. There have been few reports on the chemical synthesis of D-psicose.…”
mentioning
confidence: 99%
“…Examining the effects of D-psicose on glucose and lipid metabolism, we found that D-psicose is a sweet monosaccharide that provides no energy to growing rats and leads to less intra-abdominal fat accumulation than D-glucose and Dfructose in rats [7,8]. In addition, we suggested previously that supplemental D-psicose can lower plasma glucose levels [9]. Toyoda et al [10] suggested that Dpsicose can prevent postprandial hyperglycemia by improving the translocation of glucokinase from the nucleus to the cytoplasm in the liver of diabetic rats.…”
Section: Introductionmentioning
confidence: 77%
“…We found that Dpsicose is a sweet monosaccharide that provides no energy and leads to less body fat accumulation than Dglucose and D-fructose in rats [7,8]. In addition, we have suggested that supplemental D-psicose can lower plasma glucose levels [9]. D-Psicose is expected to have a beneficial effect in the control of blood glucose levels in type 2 diabetes.…”
Section: Groupsmentioning
confidence: 87%
“…35) By baking, a D psicose containing butter cookie has recently been shown to gain antioxidant activity due to the browning reaction. 36) D Psicose can lower plasma glucose levels and reduce body fat accumulation in rats, suggesting suppression of the hepatic lipogenic activity 37) and may also be of therapeutic value in the treatment of diseases such as atherosclerosis. 38) As a potent anthelmintic, D psicose has been shown to inhibit the motility, growth and reproductive maturity of Caenorhabditis elegans.…”
Section: D-psicosementioning
confidence: 99%